Gaya Bahasa dalam Puisi Aḥinnu ilá Khubzi Ummī Karya Mahmoud Darwish - Rahma Salbiah (Al-Ma‘rifah, 2022)
Literature is an art mediated by language, while literary works are a product of imagination with the medium of language. A poem is a literary work that has a dense language of figures and symbols. Therefore, research is needed to analyse the meaning of a poem. One of the analyses of poem research is using stylistic analysis. The poem that is the object of this study is the poem Aḥinnu ilá Khubzi Ummī by Mahmoud Darwish. This poem describes the poet's longing for his mother, which is full of figurative language. This study aims to describe the various styles of language in the poem Aḥinnu ilá Khubzi Ummī by Mahmoud Darwish. The method used is a content analysis by describing the form of language style in Mahmoud Darwish’s poem. The results of this study indicate that the author uses several language styles in the poem, which include (1) hyperbole, (2) paradox, and (3) personification.